Case Report and Literature Review of Severe Anemia Secondary to Chemotherapy Combined with PD-1 Monoclonal Antibody Immunotherapy for Lung Adenocarcinoma - Yaowen HU; Jing ZHAO; Xiaoxing GAO; Yan XU; Mengzhao WANG (Chinese Journal of Lung Cancer, 2025)
Programmed cell death 1 (PD-1) inhibitor therapy for lung adenocarcinoma may induce rare but severe hematologic adverse events, including severe anemia. Although glucocorticoids are recommended for managing immune-related adverse events, therapeutic experience with PD-1 inhibitor-induced severe anemia remains limited, and its efficacy and safety have not been fully validated. This article reports a case of advanced lung adenocarcinoma in which severe anemia developed following combination therapy with chemotherapy and PD-1 inhibitor. After comprehensive evaluation, the patient was diagnosed with anemia of inflammation (AI) and achieved significant hemoglobin recovery following high-dose glucocorticoid treatment. These findings may provide new insights into the recognition and management of this rare hematologic toxicity in clinical practice.